Extracellular vesicles in laboratory medicine: a review and outlook - Wang, Xingdong; Liu, Meijin; Zhao, Minghong; Shen, Haibin; Jin, Qing; Rao, Dingyu; Huang, Defa (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs), serving as promising novel biomarkers for diseases, demonstrate extensive potential applications in disease diagnosis, prognosis evaluation, and treatment monitoring. Currently, EVs have made substantial advancements in the areas of disease diagnosis, prognosis, and treatment. Nevertheless, for EVs to be fully integrated into clinical laboratories, ongoing efforts are required in multi-omics integration and big data analysis, the development of clinically applicable separation and detection technologies, the establishment of standardized quality systems, as well as clinical trials and regulatory approval processes. This paper reviews the current status of the application of extracellular vesicles in disease diagnosis, prognostic assessment, and treatment monitoring, analyzes the challenges facing current research, and discusses future trends.